A Systematic Review of Neuropsychological Outcomes After Treatment of Intracranial Aneurysms. Issue 6 (14th December 2022) - Nasra, Mohamed; Weerakkody, Dumindu; Maingard, Julian Tam; Hall, Jonathan; Mitreski, Goran; Kok, Hong Kuan; Smith, Paul D.; Russell, Jeremy H.; Jhamb, Ashu; Brooks, Duncan Mark; Asadi, Hamed
Abstract : BACKGROUND: Aneurysmal subarachnoid hemorrhage is a cause of profound morbidity and mortality. Its effects extend beyond functional neurological status to neurocognitive and psychological functioning. Endovascular treatment is becoming more prevalent after increasing evidence for its safety and efficacy; however, there is a relative paucity of evidence specific to neurocognitive status after treatment. OBJECTIVE: To assess and compare neuropsychological outcomes after the treatment of ruptured and unruptured intracranial aneurysms. METHODS: A systematic review of the literature was conducted searching for articles assessing the neuropsychological and cognitive outcomes after the treatment of ruptured and unruptured intracranial aneurysms. Inclusion criteria were English language, publication between January 2000 and October 2020, and discussion of neuropsychological outcomes in adequate detail. Outcomes were categorized into 8 domains: 5 Neurocognitive (Language, Executive Function, Complex Attention, Memory and Learning, and Perceptual motor function), Intelligence Quotient, Affect, and Quality of Life. RESULTS: Twenty-four articles were included comprising 2236 patients (924 surgical clipping, 1095 endovascular coiling, and 217 controls). These studies reported that most tests revealed no significant difference [n = 356/421 (84.56%)] between treatment modalities. More studies reported significantly superior test scores in the fields of language, executive function, and memory and learning after coiling [n = 53/421 tests (12.59%)] compared with clipping [n = 12/421 tests (2.85%)]. CONCLUSION: The current available data and published studies demonstrate a trend toward improved neurocognitive and psychological outcomes after endovascular treatment. Although these findings should be considered when deciding on the optimal treatment method for each patient, drawing definitive conclusions is difficult because of heterogeneity between patients and studies.